Shear Mechanical Behaviours and Multistrength Parameter Characteristics of Fault Gouge - Han Bao; Qun Qi; Hengxing Lan; Changgen Yan; Wei Xu; Xin Liu; Langping Li (Advances in Civil Engineering)
Fault gouge has special mechanical properties and remarkable engineering effects. Using a ring shear test, the strength properties of the differently colored remolded fault gouges of the Shendaogou Fault in Yan’an were studied by changing moisture contents and normal stresses. Chlorite and illite are the main clay minerals in fault gouges; differences in mineral composition make fault gouges appear in different colors. Besides clay minerals, the dried fault gouges disintegration in water is also due to the transformation of gypsum. The gradation of green fault gouge and multicolor fault gouge is better than that of the red fault gouge, while the fault gouges’ strain softening properties become weaker as the coarse grain content increases. Affected by water content and normal stress, the shear planes can be divided into three failure modes: peeling failure, grooved failure, and sliding failure. With the increase of water content, there will be a significant weakening on cohesion and friction angle. A new parameter, the “Normal Stress Threshold (NST),” is introduced as a critical value for the emergence of the strain hardening phenomenon, and the NSTs of different fault gouges are significantly different. The functions obtained from the relation of residual strength, peak strength, and normal stress can be used to calculate shear strength parameters under any normal stresses. In addition, the residual strength of fault gouge is obviously different from clay and loess, which can be qualitatively explained by clay particle contents.